2003
DOI: 10.1046/j.1365-2923.2003.01558.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning together: clinical skills teaching for medical and nursing students

Abstract: Collaborative learning opportunities for nursing and medical students are feasible and add value to the learning experience. Data indicate positive outcomes of learning in multiprofessional groups, comprising increased confidence levels, increased understanding of others' professional roles and personal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 10 publications
5
44
1
1
Order By: Relevance
“…The previous review found contextual issues that influenced the development and implementation of IPE were linked to policy and clinical drivers for IPE (Cooke et al 2003;Tucker et al 2003), organisational support to provide access to resources, such as time, space and finances (e.g. Morey et al 2002) and learner professions/numbers (Mu et al 2004).…”
Section: Ipe Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous review found contextual issues that influenced the development and implementation of IPE were linked to policy and clinical drivers for IPE (Cooke et al 2003;Tucker et al 2003), organisational support to provide access to resources, such as time, space and finances (e.g. Morey et al 2002) and learner professions/numbers (Mu et al 2004).…”
Section: Ipe Contextmentioning
confidence: 99%
“…Pollard et al 2005), age, work experience and professional background (e.g. Tucker et al 2003) could affect the delivery of IPE.…”
Section: Learner Characteristicsmentioning
confidence: 99%
“…51 Multiprofessional education for health professionals is feasible and results in positive learning outcomes such as increased interprofessional collaboration, improved communication skills, mutual respect, increased confidence levels, increased understanding of others' professional roles, and personal development. [52][53][54] Research into interprofessional and multiprofessional education specifically focusing on CAM training is lacking, although the basis for its importance exists. For example, some community pharmacists have reported that doctor's disagree with their CAM recommendation, possibly due to insufficient information, 6 leading to confusion and noncompliance by the patient.…”
Section: Discussionmentioning
confidence: 99%
“…(Weaver et al, 2014). Interdisciplinary, teambased simulation experiences lead to more effective team skills (Robertson et al, 2010;Tucker et al, 2003). In addition, utilizing simulation to enhance teamwork has been shown to enhance the quality of patient care while best preparing providers for practice (Bandali, Parker, Mummery, & Preece, 2008;Robertson & Bandali, 2008).…”
Section: Inter-professional Educationmentioning
confidence: 99%